Unlocking HAMKA's Insights on Inner Peace in Tafsir al-Azhar - Rahmah, Syarifah; Rosyadhi, Rozi Irfan (Universitas Muhammadiyah Surakarta, 2023)
This life is like a chain of problems that will continue until the world ends. So, as long as humans still live in the world, they will be faced with problems. However, what differentiates one human from another is the way they deal with problems. Some face it with anxiety, but some can get through it calmly. This calm is an essential discussion of this research. Considering that HAMKA is a mufassir and figure of Sufism, of course, his interpretation is also very much needed to find the essence of mental peace. There is also a research objective, namely, to find out the concept of mental peace according to HAMKA in the Tafsir al-Azhar book. The method used in this research is qualitative with a descriptive-analytical approach. This research uses thematic interpretive research with ontological, epistemological, and axiological analysis. After conducting research, the results were obtained, namely the concept of mental peace from the word sakinah, namely feeling optimistic because you are confident in help from Allah when facing a critical or unfavorable situation. Meanwhile, from the word ithmi'nân, mental calm is a balanced condition that a person feels. The way to achieve peace of mind is to put your trust in Allah and always recite the dhikr of Allah. Meanwhile, the positive impact of mental peace is being wise in making decisions, being kept away from feelings of anxiety, and being able to live life well. Meanwhile, the negative impact if the soul is not calm is that feelings of doubt and anxiety arise and take unwise actions because they are carried away by lust.